Interference-Adaptive Fast Dynamic Channel Allocation in TD-SCDMA System - Min, Tae Y.; Kim, Byeong C.; Kim, Joung C.; Kang, Chung G. (Wireless personal communications, 2011)
This paper proposes a new priority metric for fast dynamic channel allocation (DCA) in TD-SCDMA system, which reallocates radio resource units (RUs) to bearer services in a cell. It allows for developing a new interference-adaptive fast DCA algorithm, which is more flexible with a non-uniform user distribution. It considers the relative transmission opportunities with respect to the residual capacity and co-channel interference levels for all users, which steadily varies in the real communication environment. The proposed fast DCA algorithm aims to fully utilize the physical resource available in the time-division duplexing (TDD)-based CDMA system subject to the various types of inter-cell interference, as opposed to most existing algorithms in which traffic load and quality of service cannot be jointly balanced among the multiple radio resource units in a flexible manner. The simulation results show that the proposed algorithm improves the outage performance while reducing the average system interference, achieving full utilization of the physical resource, i.e., 48 RUs in TD-SCDMA, over a wide range of acceptable outage performance.